Features of the complement system in primary open-angle glaucoma and dry eye syndrome in the elderly - N. M. Agarkov; S. L. Fabrikantov; I. V. Lev; S. I. Nikolashin; V. V. Aksenov (Медицинская иммунология, 2022)
Primary open-angle glaucoma combined with dry eye syndrome is the leading cause of irreversible blindness. Complement system remains nearly unexplored in this disorder. The aim of our study was to evaluate the parameters of complement system in primary open-angle glaucoma and dry eye syndrome among elderly persons. The study was conducted at the S. Fedorov Center of Eye Microsurgery (Tambov Branch), and enrolled 62 patients aged 60 to 74 years with primary open-angle glaucoma combined with dry eye syndrome, and 33 patients free of this pathology. The blood complement system was studied by hemolytic method and enzyme immunoassay, and the C1 inhibitor was studied by chromogenic method. To assess possible contribution of the complement system components to the mentioned eye disorder, appropriate odds ratios were calculated, according to the generally accepted method. The study of blood complement system in elderly patients with combined primary open-angle glaucoma and dry eye syndrome have shown, first of all, high C3a level (up to 106.2±3.9 ng/ml), increased contents of C5a (4.5±0.2 ng/ml), and factor H (215.9±5.2 mcg/ml), along with decreased C1 inhibitor (to 168.4±6.1 mcg/ml). In the age-matched control group, the contents of appropriate plasma complement factors were, respectively, 45.2±4.0 ng/ml; 3.1±0.2 ng/ml; 141.5±4.3 mcg/ml; 237.9±5.8 mcg/ml, showing significant difference for all these parameters. An important pathogenetic role of C3a component, C5a component, factor H, and the C1 inhibitor in development of combined primary openangle glaucoma with dry eye syndrome was confirmed by the values of odds ratio (OR) with maximum value for the C3a component (OR 4.035, CI 3.640-4.283, p < 0.0001), which indicates increased risk of developing the mentioned ophthalmopathology in old age. High odd ratios were also characteristic of C5a blood components (2.946; CI 2.618-3.547), C3 (2.821; CI 2.453-3.264), factor H (2.765; CI 2.431-3.148). Less significant changes were revealed for other complement components thus suggesting only marginal association with development of primary open-angle glaucoma with dry eye syndrome in old age This indicates that the development of primary open-angle glaucoma with dry eye syndrome is associated with activation of these factors of the complement system. The revealed features of the complement system will enable us for more effective diagnostics of these combined eye disorders.